TEACHER’S STRATEGIES IN TEACHING WRITING RECOUNT TEXT AT SMP GAJAH MADA MEDAN - Sri Rejeki Ganda Ria; Isli Iriani Indiah Pane (Universitas Negeri Medan, 2022)
The aims of this study were to investigate teacher’s strategies in teaching writing recount text at SMP GAJAH MADA MEDAN and to discover the reasons on why teacher implemented that teaching strategies the way he did in an online class. The method of this research was qualitative research. The technique of data collection in this research were observation and interview. The research finding showed that the teacher applied two strategies in teahing writing namely Shared Writing Strategy and Guided Wring Strategy. According to the teacher, the reasons for using Shared Writing Strategy and Guided Writing Strategy are these strategies are suitable and effective to overcome students difficulties in writing especially in an online class that more complicated than face to face learning. Both of these strategies also made the students easily to understand the lesson and become more independent to write their own recount text.